Les inondations du 15 juin 2010 dans le Centre Var : réflexion sur un épisode exceptionnel. Études de Géographie Physique, n° XXXVII-2010, p. 41-76. - Claude Martin (Physio-Géo)
The hydrological event which affected the Var Department on 15th June 2010 must be considered as very exceptional. The return periods of daily rainfalls are more than millennial and those of peak discharges are at least multi-centennial. After 200 mm of rainfall, rivers presented a flash rising of flood, extremely fast (15 minutes) and violent. This response is in relation with the behaviour of karstic areas, which were largely saturated. Some practises of management (streams covered by a street or a place, too easily flooded bridges, residential and commercial areas located along streams or in dangerous flood areas) took part in exacerbating the consequences of this event. If certain measures can reduce the devastating effects of a so important event, it is also necessary to accept to deal with a risk which can be out of control.The attached file provides the full paper in a single-column version. The few changes to the original paper are indicated by dark blue.